IMPLEMENTASI RAPID MINER PADA ANALISA KETEPATAN BIDANG PEKERJAAN ALUMNI PRODI TEKNIK INFORMATIKA STMIK NURDIN HAMZAH JAMBI: ALUMNI, DATA MINING, PRODI TEKNIK INFORMATIKA, K-MEANS, STMIK NURDIN HAMZAH. - Wahyuning Astuti, Reny; Puspitorini, Sukma; Kurnia Akbar, Fajri (FORTECH (Journal of Information Technology), 2019)
Sekolah Tinggi Manajemen Informatika dan Komputer (STMIK) Nurdin Hamzah Jambi is a college that organizes academic education in the discipline of information technology. Every year STMIK always produces scholars who have qualified abilities. However, with the graduation rate in Jambi always increasing, the worries of students who are still running lectures get jobs that are suitable for their field of expertise. Therefore, an analysis is needed to see the level of accuracy of the work obtained by the alumni of Tekhnik Informtika STMIK Nurdin Hamzah Jambi. The purpose of this study was to find out the level of accuracy of the work of alumni of Teknik Informatika STMIK Nurdin Hamzah Jambi using the K-Means method. This analysis is assisted by using the Rapidminer with its input is the alumni identity, current employment data and expertise data after graduating from Teknik Informatika STMIK Nurdin Hamzah. The process in this analysis is carried out with data that has been given the value of each answer of alumni data in the K-Means method to obtain a Cluster is inappropriate, precise and very precise. The results of this study out of 100 alumni data obtained, 48 alumni entered the Cluster incorrectly, 35 precise Clusters and 17 Clusters were very precise.